Organizational learning on coopetition strategy: an exploratory research on a Turkish private banks credit card application - ARZOVA, SABRİ BURAK (ELSEVIER SCIENCE BV, 2013)
In the Turkish banking sector, competition and the banks' costs have become more important than ever due to the global financial crisis which began at 2008 and affected the world economic and financial systems. The banks, aim to increase their share in the credit card market which is one of the most profitable market in the sector, are cooperated with the other banks which have well-known credit card brand and wide POS network. This strategy is called as coopetition. The primary goal of the coopetition is to increase the market share M the sector. However, organizational learning M the credit card market is the other important advantage of coopetition. In this research, we explored the relationship between coopetition and organizational learning. For this purpose, two semi structured interviews were made with the manager of operation and information technology in the bank which has applied coopetition to increase its credit card market share in the Turkish banking sector since 2007. With these interviews, the effect of coopetition on organizational learning has been explored. On the other hand the importance of documentation and communication on organizational learning, the effect of coopetition on people, information system and organizational process of the bank were also explored in this study.
Keywords: Coopetition; Organizational learning; Turkish credit card market; CO-OPETITION; PERSPECTIVE